Students' Experiences In Accessing Bookless Library Services: : A Phenomenological Study At Universitas Negeri Makassar - Fauzan Hidayatullah; Aryana Dwi Putra Kadek (Department Library of Governance Institut of Home Affairs, 2026)
Background: Digital transformation in higher education has encouraged the development of bookless library services as a flexible means of accessing academic information. However, previous studies have predominantly focused on service quality, technology acceptance, and user satisfaction, while students’ lived experiences as primary users of digital library services remain underexplored. Purpose: This study aims to understand students’ experiences in accessing bookless library services at Universitas Negeri Makassar. Method: This study employed a qualitative approach with a descriptive phenomenological design. Eight students from different faculties and academic levels were selected through purposive sampling. Data were collected through in-depth interviews, limited participatory observation, and document review. Data analysis involved phenomenological reduction, identification of meaning units, theme development, and interpretation of participants’ experiences. Result: The findings revealed four major themes: (1) digital access as an extension of learning space and time, providing greater flexibility in obtaining academic resources; (2) the need for orientation in navigating interfaces and information retrieval pathways, as students still encounter difficulties in understanding available features; (3) the institutional repository as the most meaningful academic resource for thesis preparation and reference searching; and (4) technical barriers and digital literacy disparities that influence the effectiveness of service utilization. Conclusion: The mobile library service plays a significant role in meeting the information needs of female inmates, but improvements are needed through collection diversification, increased procurement frequency, and the implementation of information literacy programs to make the service more relevant to their needs. Bookless library services have become an important part of students’ academic experiences by supporting flexible access to information and learning resources. Nevertheless, interface simplification, infrastructure improvement, and continuous information literacy programs are needed to optimize service utilization and enhance user experience.